Analysis of Techniques in Laparoscopic Inguinal Hernia Repairs across Pediatric Age Groups: EUPSA Trainees of European Pediatric Surgery Survey - Ulman, Hilmican; Aubert, Ophelia; Wiernik, Agnieszka; Moreno-Alfonso, Julio César; Gazzaneo, Marta; Sterlin, Alexander; Saxena, Amulya K. (European Journal of Pediatric Surgery, 2024)
Aim This survey analyzed techniques in laparoscopic inguinal hernia repair (LIHR) across pediatric age groups.Materials and Methods Data were collected through an online survey for pediatric surgeons, comprising of 38 questions, conducted by the European Pediatric Surgeons' Association (EUPSA) Trainees of European Pediatric Surgery (TEPS) LIHR Working Group.Results The survey was completed by 183 surgeons from 22 countries. Seventy-seven percent of respondents had performed LIHR at least once. Regarding preferences about the patient's gender, 7% respondents perform LIHR only in selected females, 9% routinely in females, 15% in both genders with age/weight restrictions, 24% routinely in both genders, 31% in selected cases, and 14% never perform LIHR. Percutaneous internal ring suturing (PIRS) was the preferred technique in all age groups, with totally extraperitoneal and transabdominal preperitoneal repairs preferred by 9% in adolescents. The majority (59%) repaired a contralateral patent processus vaginalis if present. Hydro-dissection (21%) and additional intra-abdominal instruments (42%) were preferred more often for male patients. The distal hernia sac was left intact by most respondents (92%). Responses regarding recurrence rates varied: 40% responded that LIHR had recurrence rates comparable to open surgery, whereas 10% reported increased recurrences and hence limited its use, and 10% consider that slightly increased recurrences are outweighed by lower complication rates associated with laparoscopic methods and thus continue LIHR.Conclusions PIRS is the preferred choice for pediatric LIHR. Surgical techniques vary and are influenced by patient gender and age. The survey gives insights into demographics, case selection, and approaches among pediatric surgeons with regard to LIHR.
Keywords: minimally invasive surgical procedures; laparoscopy; inguinal hernia; child; surveys and questionnaires